2022
DOI: 10.1007/s10661-022-09913-w
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of the protective measures taken for the COVID-19 pandemic on water consumption and post meter leakages in public places

Abstract: Adequate, secure, and sustainable water supply gained utmost importance as an essential public service during the COVID-19 pandemic. The aim of this research study is to investigate impacts of the protective measures taken for the COVID-19 pandemic on water consumption and post meter leakages in public places. A total of 22 pilot study sites (PSS) representing schools, graveyards, parks, mosques, public toilets, a university building, and a sport facility were chosen to apply this study. The PSS were equipped … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Likewise, in Xie et al [57], an augmented reality system was successfully applied to facilities' inspection and maintenance by highlighting failed assets and supporting other FM functions (recording, communication, and verification). Other studies have also advocated the use of innovative systems to ensure SFM practices [18,69].…”
Section: Innovative Maintenance Managementmentioning
confidence: 99%
See 1 more Smart Citation
“…Likewise, in Xie et al [57], an augmented reality system was successfully applied to facilities' inspection and maintenance by highlighting failed assets and supporting other FM functions (recording, communication, and verification). Other studies have also advocated the use of innovative systems to ensure SFM practices [18,69].…”
Section: Innovative Maintenance Managementmentioning
confidence: 99%
“…Further, some of the least frequently occurring keywords, such as machine learning, post-pandemic, and life cycle costing, did not appear in the clusters. One study was found through hand searching that dwelt on water management in public places during the COVID-19 pandemic [69]. More collaborative research is therefore needed on these areas, as they are topical and will influence workplace core business processes in the future.…”
Section: Knowledge Pathwaysmentioning
confidence: 99%
“…The impact of climate change on water management in the agriculture sector attracted the most attention. Some researchers designed smart irrigation decision support systems that estimate weekly irrigation needs (Navarro-Hellín et al, 2016). Others used dynamic system models to analyze irrigation management processes that improve the efficacy of water resource allocation in times of drought (Wu et al, 2017).…”
Section: Synergies Of Multiple Sustainable Development Goals (T9)mentioning
confidence: 99%
“…Research on T4, water scarcity, and water leakage mainly refers to using smart solutions to improve water use efficiency (e.g., water leakage monitoring), by which water companies' interests can be improved (Ali et al, 2022;A. Muhammetoglu et al, 2020; & H. Muhammetoglu, 2022). This denotes that some driving forces, such as legal obligations and financial interests, are needed to urge smart water management researchers to focus on other targets of SDG 6.…”
Section: Covering All Sdg Targets For Overall Water Sustainabilitymentioning
confidence: 99%